A method for quantitatively adjusting the wear resistance of a diamond composite polycrystalline layer

By using cobalt powder with different morphology in polycrystalline diamond composite sheets, the assembly and sintering process under ultra-high pressure and high temperature conditions was adjusted, and the wear resistance instability caused by cobalt was solved, and the PDC composite sheets was pooled is achieved Accurate quantity regulation of crystal layer wear resistance.

CN115889764BActive Publication Date: 2025-02-18UNIV OF SCI & TECH BEIJING
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211566774.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-07
Publication Date
2025-02-18
Estimated Expiration
2042-12-07

AI Technical Summary

Technical Problem

Although the presence of cobalt helps to improve wear resistance when preparing polycrystalline diamond composite sheets, its thermal catalyticity and high thermal expansion coefficient may lead to graphitization of diamonds and intergranular cracking damage, resulting in unstable wear resistance and product failure.

Method used

By selecting spherical and needle-shaped cobalt powder, mixing evenly according to different weight ratios, mixing it into diamond powder, assembled with cemented carbide cylinders, and synthesized under ultra-high pressure and high temperature conditions to achieve wear resistance to the polycrystalline layer quantitative regulation.

Benefits of technology

By adjusting the morphology and proportion of cobalt powder, the wear resistance of the PDC composite sheet can be accurately adjusted, avoiding the poor wear resistance and product failure caused by excessive cobalt, and meeting the wear resistance requirements of different application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115889764B_ABST
    Figure CN115889764B_ABST
Patent Text Reader

Abstract

A method for quantitatively adjusting the wear resistance of a diamond composite sheet polycrystalline layer belongs to the field of metal materials. Spherical cobalt powder and needle-shaped cobalt powder are mixed in a ratio of 0.1-10, and then mixed with diamond micropowder in a ratio of 0.5%-10% and loaded into a metal cup, and then. The shaft end of a cemented carbide cylinder is inserted into the mixed micropowder, and a PDC composite sheet blank is synthesized under ultra-high pressure and high temperature conditions. All metal cups wrapped on its surface are then removed by sandblasting, the thickness of the diamond polycrystalline layer is adjusted to a predetermined size, and the outer diameter of the diamond composite sheet is processed to a predetermined size by a grinder, so that a finished PDC with a desired shape and size specification can be obtained after mechanical processing. The present invention mixes spherical cobalt powder and needle-shaped cobalt powder, adds them to diamond micropowder, assembles them with a cemented carbide cylinder, and realizes precise control of the wear resistance of the polycrystalline layer of the PDC product synthesized under HPHT conditions, which can meet the requirements of PDC wear resistance in various application scenarios.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal materials and relates to a method for preparing a diamond composite sheet, in particular to a new technology for accurately and quantitatively adjusting the wear resistance of its polycrystalline layer. Technical Background

[0002] Polycrystalline Diamond Compact (PDC) is an integrated composite material formed by sintering diamond micropowder and cemented carbide under ultra-high pressure (6-8GPa) and high temperature (1350-1500℃), in which the polycrystalline layer is mainly responsible for providing ultra-high wear resistance and cutting ability, while the cemented carbide is responsible for providing good impact toughness and supporting strength. Cobalt powder, as the most commonly used binder, is often used in the sintering synthesis of cemented carbide and polycrystalline layer. In the prepared PDC composite sheet, whether it is WC cemented carbide or diamond polycrystalline layer, its macroscopic properties such as strength and hardness are theoretically mainly determined by the grain size and morphology of WC or diamond grains and cobalt components. In the sintering preparation process of this product, cobalt usually plays an important role as a commonly used binder. In addition to playing a key bonding and strengthening role in the sintering reaction of WC cemented carbide, it also plays a key role in the bonding reaction of DD bonds between diamond grains in the polycrystalline layer. There have been many research reports on the effect of cobalt on the performance of WC cemented carbide. As for its effect on the performance of the polycrystalline layer, predecessors have also done some exploration and research, and obtained meaningful rules. For example, the cobalt content significantly affects the wear resistance, heat resistance and other properties of the PDC composite sheet. In the sintering process of polycrystalline diamond composite sheets, cobalt, as an important sintering medium, mainly comes from the cemented carbide support, and sometimes cobalt powder is added to supplement the cobalt source. With the complexity, diversification and special needs of the application scenarios of composite sheets, the wear resistance requirements of the composite sheets are not so high. For some formations, cobalt powder can be added to provide a cobalt source to supplement the unique control requirements of the ultra-high pressure and high temperature (HPHT) sintering process that is more demanding for the classic sweeping method.

[0003] Cobalt is an important sintering medium for PDC and is indispensable. However, due to its special physical and chemical properties, it has two sides, namely, its outstanding thermal catalytic properties for diamond may lead to graphitization of diamond during drilling and grinding, and its significantly higher thermal expansion coefficient may cause expansion and cracking damage between diamond grains. Therefore, how to ensure the comprehensive performance requirements of PDC composite sheets is a challenging problem. The addition of cobalt sources can achieve precise addition of fixed points and quantities, which is very convenient. However, in actual production, due to the problems of oxidation, moisture absorption, adhesion and agglomeration, and wide distribution of externally added cobalt powder, it is usually only used as an auxiliary means. In addition, due to the large difference in thermal expansion coefficients between cobalt and diamond matrix, during the high temperature and high pressure sintering process, the presence of excessive Co will cause the PDC composite sheet to have poor wear resistance, tooth collapse, delamination, fracture and other failure problems during use. Therefore, it is very important to strictly control the cobalt content and its cobalt dispersion, uniformity and particle morphology of cobalt powder during the preparation process.

[0004] At present, most technologies for regulating the wear resistance of the polycrystalline layer of PDC are mainly achieved through diamond powder formulation, synthesis process, external additives, etc. Among them, the amount of external cobalt is relatively simple and convenient, so it is often adopted first. However, due to the adjustment of the wear resistance of PDC, the amount of cobalt doping is always limited, so the optimization and improvement of the cobalt doping method is very important. Therefore, the commonly used method of adjusting the wear resistance of the polycrystalline layer by the amount of external cobalt powder always has certain limitations, especially the quantitative control technology of the wear resistance of the polycrystalline layer of the PDC composite sheet by the characteristics of cobalt powder morphology, which has not been reported. Summary of the invention

[0005] The present invention discloses a method for quantitatively controlling the wear resistance of diamond polycrystalline composite sheets by utilizing the special morphological characteristics of cobalt powder. Specifically, spherical cobalt powder and needle-shaped cobalt powder are selected, mixed in different proportions, and mixed evenly. Then, they are assembled with cemented carbide cylinders in a certain way and processed under ultra-high pressure and high temperature (HPHT) conditions to produce diamond polycrystalline composite sheets with different wear resistances.

[0006] The technical solution of the present invention is: a method for quantitatively adjusting the wear resistance of a polycrystalline layer of a diamond composite sheet, characterized in that:

[0007] 1) Selecting a mixed micro powder of spherical cobalt powder and needle-shaped cobalt powder, wherein the particle size of the spherical cobalt powder is between 1-10 microns; the length of the needle-shaped cobalt powder is between 1-10 microns, and the radial size is between 1-5 microns;

[0008] 2) Weighing and mixing the spherical cobalt powder and the needle-shaped cobalt powder respectively in a weight ratio of 0.1-10, and setting aside;

[0009] 3) Weigh the mixed micropowders above and mix them with the diamond micropowders in a weight ratio of 0.5% to 10% to obtain the mixed micropowders, and put them into a high temperature refractory metal cup;

[0010] 4) Insert the shaft end of the cemented carbide cylinder into a high-temperature refractory metal cup filled with mixed micropowder, and synthesize it in a six-sided top pressure under certain ultra-high pressure and high temperature conditions to obtain a PDC composite sheet blank.

[0011] 5) In step 4, the blank is first sandblasted to remove all metal cups wrapped on its surface, and then the thickness of the diamond polycrystalline layer is adjusted to a predetermined size by grinding, and the outer diameter of the diamond composite sheet is processed to a predetermined size by a grinder, so that a finished PDC with the desired shape and size specifications can be obtained after mechanical processing.

[0012] Furthermore, in step 2), the ratios of the spherical cobalt powder to the needle-shaped cobalt powder are 1:0.1, 1:0.5, 1:1, 1:2, 1:5, and 1:10, respectively.

[0013] Furthermore, in step 3), the weight ratios of the mixed micropowder and the diamond micropowder are 1%, 2%, 3% and 5% respectively.

[0014] Furthermore, the specific preparation method of the blank in step 4) is as follows: depending on the size of the composite sheet, weigh more than 1.5-5 grams of mixed micro-powder, put it into the bottom of a cylindrical cup (called an inner cup) of high-temperature refractory metal niobium (or zirconium, molybdenum, tantalum, titanium), and gently vibrate it to make it evenly flat and dense to form a flat powder layer; then gently place one axial end of a cemented carbide cylinder (cobalt content 10-16%) on the surface of the powder layer to make it fully contact, wherein the size of the inner cup is larger than that of the cylindrical The diameter of the cemented carbide is 5-25 microns larger, and then another high-temperature refractory metal niobium (or zirconium, molybdenum, tantalum, titanium) metal cup (called the outer cup) that is 10-50 microns larger than the diameter of the cemented carbide cylinder is buckled onto the cemented carbide cylinder together with the inner cup and wrapped tightly together to form the so-called inner core; after the above inner core is loaded into a conventional pyrophyllite pressure transfer block, it is pressed at an ultra-high pressure of 6-8GPa and sintered at a high temperature in the high temperature range of 1300-1700°C to obtain a blank.

[0015] The key points and innovations of the above invention content lie in the correct mixing of spherical cobalt powder and needle-shaped cobalt powder, which are added to diamond micropowder to assemble with cemented carbide cylinders, and realize relatively precise quantitative control changes in the wear resistance of the polycrystalline layer of the PDC product synthesized under HPHT conditions to meet the specific requirements of PDC wear resistance in various application scenarios. The wear ratio results of the synthesized PDC are respectivelyFigure 1 , Figure 2 , Figure 3 As shown, it can be seen that there is a good linear correspondence between the mixing ratio of cobalt powder and the wear ratio result of the vertical lathe test, so the purpose of adjusting the mixing ratio of cobalt powder morphology to more accurately and quantitatively control the wear resistance of PDC is achieved, providing a convenient new technology for accurately controlling the wear resistance of PDC. The wear resistance result test of PDC mentioned in the present invention uses the ratio of the wear amount of the polycrystalline layer corresponding to the grinding of a certain amount of granite on the surface of a granite frustum-shaped grinding disc rotating at a constant speed with a certain contact angle and contact area as a reference value.

[0016] The significant technical increments of the present invention compared with the prior art are:

[0017] (1) The present invention provides a novel quantitative control method for adjusting the wear resistance of the PDC polycrystalline layer. Few people have used the difference in the morphological characteristics of cobalt powder to achieve quantitative control of the wear resistance of the polycrystalline layer, but the present invention discloses a new method that cleverly uses the morphology of cobalt powder to achieve the wear resistance adjustment of the polycrystalline layer.

[0018] (2) The present invention is a breakthrough in the traditional idea of ​​adjusting the wear resistance of the polycrystalline layer by changing the cobalt powder content. The existing method of adjusting the wear resistance of the polycrystalline layer by cobalt powder is mainly to adjust the amount of cobalt powder added.

[0019] At present, there is no specific and clear specification and description of the morphology of cobalt powder, which often leads to the same amount of cobalt powder being added but the same wear resistance cannot be obtained. This wear resistance fluctuation caused by ignoring the morphology of cobalt powder is a negative factor for the stability and quality consistency of PDC products. The present invention puts forward specific requirements for the consistency of the morphological characteristics of cobalt powder, which is conducive to solving the wear resistance stability and consistency problems of the polycrystalline layer.

[0020] (3) The present invention proposes a free regulation method, that is, by combining two cobalt powders of different morphologies in different weight ratios, to achieve quantitative regulation of the wear resistance of the PDC polycrystalline layer, thereby meeting the special requirements for PDC wear resistance in different application scenarios. This is a special new regulation method that has not been shown in previous literature reports and public documents. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 These are the corresponding wear ratio results when pure spherical cobalt powder is added in different weight proportions in the present invention.

[0022] Figure 2 These are the corresponding wear ratio results when pure needle-shaped cobalt powder is added in different weight proportions in the present invention.

[0023] Figure 3It is the wear ratio corresponding to the different weight ratios of spherical / needle-shaped cobalt powder when 1%, 1.5% and 2% of mixed cobalt powder are added (the number of vertical lathe turns is fixed at 25 turns). DETAILED DESCRIPTION

[0024] The following specific implementation cases are intended to demonstrate the operating principles and technical points to be disclosed by the present invention in a more specific and detailed manner. The disclosed case is not intended to limit or restrict the scope of protection of the rights covered by the patent disclosure principles and technologies of the present invention.

[0025] Implementation 1:

[0026] Spherical cobalt powder with an average particle size of 2.5 microns is selected; needle-shaped cobalt powder with an average length of 10 microns and an average radial size of 3 microns is selected; the two cobalt powders are weighed in a weight ratio of 1:1 and mixed evenly; then the mixed powders are mixed with the prepared diamond powder in a weight ratio of 1%, and mixed again to make them evenly mixed; the mixed powders are accurately weighed and put into a high-temperature resistant metal cup such as a niobium cup together with a cemented carbide cylinder (φ16mm×13mm), and synthesized in a six-sided top press under ultra-high pressure of 6GPa and high temperature of 1400℃. After keeping the temperature and pressure for 15 minutes, the PDC composite sheet blank is obtained by cooling and unloading the pressure. After mechanical processing such as turning, chamfering, and polishing, a finished PDC with a standard shape and size can be obtained. After the sample was chamfered to 0.40mm, the wear resistance test was carried out on a granite vertical lathe, and the wear ratios corresponding to different numbers of laps were measured, of which the wear ratio of the 25th lap was 1.28 million. Compared with the corresponding wear ratio of 1.4 million for PDC synthesized by adding 1% pure spherical cobalt powder and 1.14 million for PDC synthesized by adding 1% pure needle-shaped cobalt powder, the wear resistance of the PDC synthesized by adding the mixed cobalt powder was appropriately adjusted, which was between the two.

[0027] Implementation 2:

[0028] Spherical cobalt powder with an average particle size of 2.5 microns is selected; needle-shaped cobalt powder with an average length of 10 microns and an average radial size of 3 microns is selected; the two cobalt powders are weighed in a weight ratio of 1:2 and then mixed evenly; the mixed micropowders are then mixed with the prepared diamond micropowder in a weight ratio of 1%, and mixed again to make them evenly mixed; the mixed micropowders are accurately weighed and placed in a high-temperature resistant metal cup such as a niobium cup together with a cemented carbide cylinder (φ16mm×13mm), and synthesized in a six-sided top press under ultra-high pressure of 6GPa and high temperature of 1400℃. After keeping the temperature and pressure for 15 minutes, the PDC composite sheet blank is obtained by cooling and unloading the pressure. After mechanical processing such as turning, chamfering, and polishing, a finished PDC with a standard shape and size can be obtained. After the sample was chamfered to 0.40mm, the wear resistance test was carried out on a granite vertical lathe, and the wear ratios corresponding to different numbers of laps were measured, of which the wear ratio of the 25th lap was 1.22 million. Compared with the corresponding wear ratio of 1.4 million for PDC synthesized by adding 1% pure spherical cobalt powder and 1.14 million for PDC synthesized by adding 1% pure needle-shaped cobalt powder, the wear resistance of the PDC synthesized by adding the mixed cobalt powder was appropriately adjusted, which was between the two.

[0029] Implementation 3:

[0030] Spherical cobalt powder with an average particle size of 2.5 microns is selected; needle-shaped cobalt powder with an average length of 10 microns and an average radial size of 3 microns is selected; the two cobalt powders are weighed at a weight ratio of 1:5 and then mixed evenly; the mixed micropowders are then mixed with the prepared diamond micropowder at a weight ratio of 1%, and mixed evenly again; the mixed micropowders are accurately weighed and placed in a high-temperature resistant metal cup such as a niobium cup together with a cemented carbide cylinder (φ16mm×13mm), and synthesized in a six-sided top press under ultra-high pressure of 6GPa and high temperature of 1400℃. After keeping the temperature and pressure for 15 minutes, the PDC composite sheet blank is obtained by cooling and unloading the pressure. After mechanical processing such as turning, chamfering, and polishing, a finished PDC with a standard shape and size can be obtained. After the sample was chamfered to 0.40mm, the wear resistance test was carried out on a granite vertical lathe, and the wear ratios corresponding to different numbers of turns were measured, of which the wear ratio of the 25th turn was 1.17 million. Compared with the corresponding wear ratio of 1.4 million for PDC synthesized by adding 1% pure spherical cobalt powder and 1.14 million for PDC synthesized by adding 1% pure needle-shaped cobalt powder, the wear resistance of the PDC synthesized by adding the mixed cobalt powder was appropriately adjusted and was between the two.

[0031] Implementation 4:

[0032] Spherical cobalt powder with an average particle size of 2.5 microns is selected; needle-shaped cobalt powder with an average length of 10 microns and an average radial size of 3 microns is selected; the two cobalt powders are weighed in a weight ratio of 1:2 and then mixed evenly; the mixed micropowders are then mixed with the prepared diamond micropowder in a weight ratio of 2%, and mixed evenly; the mixed micropowders are accurately weighed and placed in a high-temperature resistant metal cup such as a niobium cup together with a cemented carbide cylinder (φ16mm×13mm), and synthesized in a six-sided top press under ultra-high pressure of 6GPa and high temperature of 1400℃. After keeping the temperature and pressure for 15 minutes, the PDC composite sheet blank is obtained by cooling and unloading the pressure. After mechanical processing such as turning, chamfering, and polishing, a finished PDC with a standard shape and size can be obtained. After the sample was chamfered to 0.40mm, the wear resistance test was carried out on a granite vertical lathe, and the wear ratios corresponding to different numbers of turns were measured, of which the wear ratio of the 25th turn was 1.05 million. Compared with the corresponding wear ratio of 1.4 million for PDC synthesized by adding 1% pure spherical cobalt powder and 1.14 million for PDC synthesized by adding 1% pure needle-shaped cobalt powder, the wear resistance of the PDC synthesized by adding the mixed cobalt powder was appropriately adjusted and was between the two.

Claims

1. A method for quantitatively adjusting the wear resistance of a polycrystalline layer of a diamond composite sheet, characterized in that: 1) Selecting a mixed micro powder of spherical cobalt powder and needle-shaped cobalt powder, wherein the particle size of the spherical cobalt powder is between 1-10 microns; the length of the needle-shaped cobalt powder is between 1-10 microns, and the radial size is between 1-5 microns; 2) Weighing and mixing the spherical cobalt powder and the needle-shaped cobalt powder respectively in a weight ratio of 0.1-10, and setting aside; 3) Mix the above mixed powders with diamond powder in a weight ratio of 0.5%-10%. Weighing and mixing with diamond micropowder to obtain mixed micropowder and putting it into a high temperature resistant refractory metal cup; 4) Insert the shaft end of the cemented carbide cylinder into the high temperature refractory metal containing mixed micro powder. In the cup, under certain ultra-high pressure and high temperature conditions, it is synthesized in the six-sided top pressure to obtain the PDC composite sheet blank; 5) The blank of step 4) is firstly sandblasted to remove all metal cups wrapped on its surface, and then the thickness of the diamond polycrystalline layer is adjusted to a predetermined size by grinding, and the outer diameter of the diamond composite sheet is processed to a predetermined size by a grinder, so that a finished PDC with the desired shape and size specifications can be obtained after mechanical processing.

2. A method for quantitatively adjusting the wear resistance of a polycrystalline layer of a diamond composite sheet as claimed in claim 1, characterized in that: The particle size of the spherical cobalt powder in step 1) is between 1 and 10 microns; the length of the needle-shaped cobalt powder is between 1 and 10 microns, and the radial size is between 1 and 5 microns.

3. A method for quantitatively adjusting the wear resistance of a polycrystalline layer of a diamond composite sheet as claimed in claim 1, characterized in that: Step 2) The weight ratio of the spherical cobalt powder to the needle-shaped cobalt powder can be selected from the following: 1:0.1, 1:0.5, 1:1, 1:2, 1:5, 1:

10.

4. A method for quantitatively adjusting the wear resistance of a polycrystalline layer of a diamond composite sheet as claimed in claim 1, characterized in that: Step 3) The weight ratio of the mixed micropowder to the diamond micropowder can be selected from the following: 1%, 2%, 3%, 5%.

5. The method for quantitatively adjusting the wear resistance of a polycrystalline layer of a diamond composite sheet according to claim 1, characterized in that: Step 4) The specific preparation method of the blank is as follows: depending on the size of the composite sheet, weigh more than 1.5-5 grams of mixed micropowder, load it into the bottom of a cylindrical inner cup of high-temperature refractory metal niobium or zirconium, molybdenum, tantalum, and titanium, and gently vibrate it to make it evenly flat and dense to form a flat powder pile; then gently place one axial end of a cemented carbide cylinder with a cobalt content of 10-16% on the surface of the powder pile to make it fully contact, wherein the size of the inner cup is 5-25 microns larger than the diameter of the cylindrical cemented carbide, and then buckle another high-temperature refractory metal niobium or zirconium, molybdenum, tantalum, and titanium cup that is 10-50 microns larger than the diameter of the cylindrical cemented carbide cylinder onto the cemented carbide cylinder and the inner cup to wrap it tightly, that is, assemble it into an inner core; after the above inner core is loaded into a conventional pyrophyllite pressure transfer block, it is subjected to ultra-high pressure pressing of 6-8GPa and high-temperature sintering at 1300-1700°C to obtain a blank.

Citation Information

Patent Citations

  • Method for manufacturing polycrystalline diamond compact enhanced by chemical vapor deposition (CVD) diamond

    CN102700191A

  • Self-sharpening polycrystalline diamond compact and preparation method thereof

    CN103722174A